Self-care management education increase quality of life of patient with chronic kidney disease undergoing hemodilysis - Dani Prastiwi; Nonik Eka Martyastuti; Isrofah Isrofah; Barzen Alisyahbana (Universitas Muhammadiyah Semarang, 2022)
Chronic kidney disease and its progression to terminal disease are a significant source of decreased quality of life. One of the efforts that can be done to improve the quality of life is self-care management. This research is Quasy Experiment research with one group pre and post-test design. Twenty-nine people were involved as respondents. The KDQoL SFTM 1.3 questionnaire was used to measure the quality of life before and after treatment. Data were analyzed using paired sample t-test. The average quality of life pretest score was 50.80 ± 8.47 and the average quality of life post-test score was 56.56 ± 10.13 with p-value = 0.024 <0.05. There is an effect of self-care management on the quality of life of patients with chronic kidney disease undergoing hemodialysis. Nursing practice to improve services by providing self-care management education in a programmed and comprehensive manner in patients with chronic kidney disease undergoing hemodialysis.